New data from the Middle Jurassic of China shed light on the phylogeny and origin of the proboscis in the Mesopsychidae (Insecta: Mecoptera) - Lin, Xiaodan (BMC Evol Biol, 2016)
BACKGROUND: The Mesopsychidae is an extinct family of Mecoptera, comprising eleven described genera from Upper Permian to Lower Cretaceous deposits. In 2009, several well-preserved mesopsychids with long proboscides were reported from the mid Mesozoic of Northeastern China, suggesting the presence of pollination mutualisms with gymnosperm plants and highlighting their elevated genus-level diversity. Since that time, additional mesopsychid taxa have been described. However, the phylogeny of genera within Mesopsychidae has not been studied formally, attributable to the limited number of well-preserved fossils. RESULTS: Here, we describe two new species, Lichnomesopsyche prochorista sp. nov. and Vitimopsyche pristina sp. nov. and revise the diagnosis of Lichnomesopsyche daohugouensis Ren, Labandeira and Shih, 2010, based on ten specimens from the latest Middle Jurassic Jiulongshan Formation of Inner Mongolia, China. After compiling data from these new fossil species and previously reported representative taxa, we conducted phylogenetic analyses and geometric morphometric studies that now shed light on the taxonomy and phylogeny of Mesopsychidae. We also evaluate the recurring origin of the siphonate proboscis in the Mecoptera and propose an evolutionary developmental model for its multiple origins. CONCLUSIONS: Phylogenetic and geometric morphometric results confirm the establishment of two new species, each to Lichnomesopsyche and Vitimopsyche. Vitimopsyche pristina sp. nov. extends the existence of the genus Vitimopsyche Novokshonov and Sukacheva, 2001, from the mid Lower Cretaceous to the latest Middle Jurassic. Two methods of analyses indicate an affiliation of Mesopsyche dobrokhotovae Novokshonov, 1997 with Permopsyche Bashkuev, 2011. A phylogenetic analysis of the Mesopsychidae supports: 1), Mesopsychidae as a monophyletic group; 2), Mesopsyche as a paraphyletic group, to be revised pending future examination of additional material; and 3), the independent origin of the proboscis in the Pseudopolycentropodidae, its subsequent loss in earliest Mesopsychidae such as Epicharmesopsyche, its re-origination in the common ancestor (or perhaps independently) in the Vitimopsyche and Lichnomesopsyche clades of the Mesopsychidae. The third conclusion indicates that the proboscis originated four or five times within early Mecoptera, whose origin is explained by an evolutionary developmental model. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-015-0575-y) contains supplementary material, which is available to authorized users.